Türkiye’de Karikatürün Dijital Dönüşümü: Uykusuz Dergisi - Uçan, Bahadır (The Turkish Online Journal of Design, Art and Communication, 2013)
Years of 2000’s can be defined as “digital age.” In this digital age, it is seen that digitalization creates new concepts and approaches and it even affects our daily lifes. Changes have seen on different areas of art both on style and contentment with digitalization. In this study,it is aimed to underline digitalization, to investigate its effects on the world of cartoons which are caricature, homour and the articles and to comment on what digitalization brings. As a popular caricature magazine in Turkey Uykusuz is selected to contrast the differences of published Uykusuz and the digitalized one that can be read on its official facebook fan page.
Keywords: Caricature; Digitalization; Homour; Article; Karikatür; Dijitalleştirme; Makale